The gender gap in STEM: evidence from Brazil - Alvarenga, Camila Rafaela (2020)
In Brazil, as in much of the world, women are underrepresented in STEM (Science, Technology, Engineering and Mathematics) majors, despite being the majority of students enrolled in tertiary education. Conversely, in primary and secondary education there exists a gender divide – favoring males – manifested in average gender diﬀerences in mathematical achievement. In order to uncover the structure of the gender gap in mathematics and establish a channel to the gender gap in STEM majors enrollment, we develop two essays. The ﬁrst essay addresses the diﬀerences in mathematical achievement in primary and secondary education with an emphasis on the unexplained part of the gap. The main result is that most of the math-gender gap is explained by non-observable gender diﬀerences in the returns to individual, family and school characteristics, such that those diﬀerence in returns increase with school grade. The second essay addresses the matter of implicit gender stereotypes in the context in tertiary education. Among other things, we ﬁnd that women in STEM are less likely to make stereotypical associations of the type, compared to women in humanities. With the aid of the literature on gender roles and stereotypes, our research results demonstrate that the subscription of individuals to gender-conforming educational paths, such as the school-grade increasing underachievement of girls in mathematics, (compared to boys), may inform the underrepresentation of women in STEM and, consequently, the gender diﬀerences observed in the labor market. Keywords: Economics.Education.Gender.